2002
DOI: 10.1242/dev.129.5.1131
|View full text |Cite
|
Sign up to set email alerts
|

MAX1andMAX2control shoot lateral branching inArabidopsis

Abstract: Plant shoots elaborate their adult form by selective control over the growth of both their primary shoot apical meristem and their axillary shoot meristems. We describe recessive mutations at two loci in Arabidopsis, MAX1 and MAX2, that affect the selective repression of axillary shoots. All the first order (but not higher order) axillary shoots initiated by mutant plants remain active, resulting in bushier shoots than those of wild type. In vegetative plants where axillary shoots develop in a basal to apical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 605 publications
(84 citation statements)
references
References 49 publications
0
62
0
4
Order By: Relevance
“…The F-box protein and an SKP1-Cullin-F-box (SCF) ubiquitin ligase protein form a complex and are involved in SL signaling [ 25 , 51 ], although the associated regulation mechanism differs between monocot and dicot plants. MAX2 forms the SCF complex in Arabidopsis with AtCullin1 and Arabidopsis serine/threonine kinase 1 (ASK1), whereas the D3 protein interacts with OsCullin1 and Oryza sativa SKP1-LIKE1/5/20 (OSK1/5/20) in rice ( Figure 1 ) [ 17 , 23 ].…”
Section: Sls Biosynthesis and Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The F-box protein and an SKP1-Cullin-F-box (SCF) ubiquitin ligase protein form a complex and are involved in SL signaling [ 25 , 51 ], although the associated regulation mechanism differs between monocot and dicot plants. MAX2 forms the SCF complex in Arabidopsis with AtCullin1 and Arabidopsis serine/threonine kinase 1 (ASK1), whereas the D3 protein interacts with OsCullin1 and Oryza sativa SKP1-LIKE1/5/20 (OSK1/5/20) in rice ( Figure 1 ) [ 17 , 23 ].…”
Section: Sls Biosynthesis and Signaling Pathwaymentioning
confidence: 99%
“…In addition to these phytohormones, SLs also appear to be involved in regulating leaf senescence because a delayed leaf senescence phenotype was found in the SL-deficient and SL-insensitive mutants ( Figure 2 ) [ 18 ]. The Arabidopsis mutants ore9 were observed with more shoot branches with delayed leaf senescence that was identical to the max2 mutant [ 51 ]. Recently, it was observed that a bamboo leaf segment showed response to GR24, confirming SL is a positive regulator in senescence.…”
Section: Sls In Controlling the Plant Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise function of D14 has not been annotated yet. MAX2, RMS4 and D3 are orthologous members of the F-box leucine-rich repeat (LRR) protein family (Stirnberg et al 2002, Ishikawa et al 2005, which probably act as a receptor for strigolactones and function in ubiquitin-mediated degradation of target proteins (Stirnberg et al 2007). Coincidentally, BRANCHED1 (BRC1) was found to be down-regulated in the Arabidopsis max mutants (Aguilar-Martinez et al 2007) and upregulated in response to application of strigolactone (Masgugycuchi et al 2009) and mutant brc1/tb1 showed an increased branching phenotype (Aguilar-Martinez et al 2007, Finlayson 2007.…”
Section: Genes Involved In the Synthesis And Signaling Pathway Of Str...mentioning
confidence: 99%
“…In recent years, strigolactone (SL) has been identified as a new type of endogenous plant hormone that inhibits shoot branching by inhibiting the growth of axillary buds [8,9]. This effect of SLs was discovered in branching mutants defective in SL signaling, including the ramosus (rms) mutants of pea (Pisum sativum) [10][11][12][13], more axillary growth (max) mutants of Arabidopsis thaliana [14][15][16], high tillering dwarf (htd) and dwarf (d) mutants of rice (Oryza sativa) [10,17] and decreased apical dominance (dad) mutants of petunia (Petunia hybrida) [18,19]. The CAROTENOID CLEAVAGE DIOXYGENASE (CCD) genes CCD7 and CCD8 were, respectively, identified as DAD1 and DAD3 in petunia, MAX3 and MAX4 in Arabidopsis, RMS5 and RMS1 in pea and D17 and D10 in rice [10,14,15,20].…”
Section: Introductionmentioning
confidence: 99%